2013
DOI: 10.1586/14737175.2013.827412
|View full text |Cite
|
Sign up to set email alerts
|

Acute ischemic stroke: comparison of low-dose and standard-dose regimes of tissue plasminogen activator

Abstract: Intravenous tissue plasminogen activator (IV-TPA), administered within 4.5 h of symptom onset, is the only therapeutic agent approved for achieving arterial recanalization in acute ischemic stroke. Current major guidelines recommend the use of a standard dose (0.9 mg/kg bodyweight; maximum 90 mg) of IV-TPA. However, comparable efficacy of IV-TPA was demonstrated in the observational studies from Japan when a lower dose (0.6 mg/kg bodyweight; maximum 60 mg) was used and later approved by the regulatory authorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In addition, thrombolytic therapy was recently introduced to our center in 2017 at a high cost (which is still not covered by health insurance), so many patients cannot afford it. Some other studies recruited small numbers of patients, like Nguyen et al 21 who included 48 in the low-dose group versus 73 standard-dose patients; Sharma et al, 22 who included 48 low-dose patients versus 32 patients receiving the standard dose; and Zhou et al 24 who included 23 patients receiving a low dose). Second, the alteplase dose selection was not randomized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, thrombolytic therapy was recently introduced to our center in 2017 at a high cost (which is still not covered by health insurance), so many patients cannot afford it. Some other studies recruited small numbers of patients, like Nguyen et al 21 who included 48 in the low-dose group versus 73 standard-dose patients; Sharma et al, 22 who included 48 low-dose patients versus 32 patients receiving the standard dose; and Zhou et al 24 who included 23 patients receiving a low dose). Second, the alteplase dose selection was not randomized.…”
Section: Discussionmentioning
confidence: 99%
“…Chao et al 19 documented a 3 months mortality of 8% in both 0.6 and 0.9 mg/kg groups. Sharma et al, 22 in Singapore documented that there was no significant difference in the 3 months mortality between low and standard doses )10% versus 13%(. Anderson et al 20 also showed that mortality at 90 days did not differ significantly between the 2 groups )8.5% and 10.3%(.…”
Section: (mentioning
confidence: 96%
“…We could not imagine what would happen if we had administered the whole standarddose after complete recanalization was observed. Some studies showed that there was no correlation between the rtPA dose and HT [4,23,24]. However, there were opposite opinions [18,25].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the action of ischemia of brain tissue and the development of reperfusion syndrome, a cascade reaction mechanism is launched, which is accompanied by the accumulation of products of free radical oxidation [18]. Considering the fact that escalation of ROS synthesis is noted both during and after brain ischemia, the products of oxidative reactions are of particular importance in ischemia and secondary cerebral hypoxia [19][20][21][22][23]. In this regard, the antioxidant therapy is justified even in a delayed manner, since one of the main mechanisms of cell death is oxidative stress [24; 25].…”
Section: Introductionmentioning
confidence: 99%